Preparation and fluorescence properties of SiO2-coated CsPbBrI2 perovskite nanocrystals - Ma, Siyu; Zhang, Jing; An, Limin (Journal of physics. Conference series, 2023)
All-inorganic perovskite nanocrystals CsPbX3 (X=Cl, Br, I) have garnered significant interest due to their promising applications and have become a leading research subject in the field of optoelectronics. The weak stability of CsPbBrI2 perovskite nanocrystals has hindered their development, however, silica coating can effectively solve this problem. The (3-aminopropyl) triethoxysilane was used as a raw material for silica synthesis to form core-shell structured CsPbBrI2@SiO2 perovskite nanocrystals to obtain enhanced optoelectronic properties. This article reveals the narrow absorption and emission peaks, small half-height widths, 14.6 ns fluorescence lifetimes, and 106.2 meV exciton binding energies of CsPbBrI2@SiO2 perovskite nanocrystals. The results show that the core-shell structured CsPbBrI2@SiO2 perovskite nanocrystals prepared by this method have excellent fluorescence spectral properties and hold significant promise for future applications in optoelectronic devices.